Profesi Guru - Bakhrudin All Habsy; Irham Eka Maulana; Fina Alfianita; Khoirun Nisak Nurul Febrianti (Universitas Maritim AMNI Semarang, 2024)
The teaching profession is a profession that plays an important role in the development of education. Teachers are not only tasked with teaching, but also guiding and forming students’ characters. Teachers are the most influential component in creating quality educational processes and outcomes. The success of a teacher in carrying out his duties as an educator is largely determined by the competence of the teacher concerned. With such complex tasks, this profession requires special skills and various competencies to carry it out. This research aims to dig deeper into the definition of the teaching profession, social responsibility and the role of teachers. The research method used is a literature study using a qualitative approach. Various literature sources, such as books, journals and scientific articles, are used to collect related data. The research results show that teachers have a big responsibility both in the school environment and in society, with the main challenges being technological developments and inequality in educational facilities.